HUKUM EKONOMI ISLAM DI INDONESIA PADA ZAMAN KEMERDEKAAN - Ikhwan Matondang, Joni Zulhendra, Asasriwarni dan (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
Islamic economics in legal regulations in Indonesia is contained in the Elucidation of Law of the Republic of Indonesia Number 50 of 2009 concerning Amendments to Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts Letter I What is meant by